Formulation and Antibacterial Activity Testing of Face Mist Made from Red Betel Leaf (Piper Crocatum Ruiz and Pav.) Ethanol Extract Against Propionibacterium Acnes - Anggraeni, Ira; Rahmawati, Riana Putri; Besan, Emma Jayanti (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aimed to formulate and evaluate the antibacterial activity of face mist containing ethanol extract of red betel leaf (Piper crocatum Ruiz & Pav.) against Propionibacterium acnes, with the hypothesis that higher extract concentrations enhance antibacterial efficacy. Research Method: A quantitative experimental design was conducted using three formulations with extract concentrations of 15%, 25%, and 35%, alongside positive (clindamycin 300 mg) and negative (base face mist) controls. Samples were obtained from Kayen Village, Pati Regency, Indonesia. Physical evaluations included organoleptic, homogeneity, pH, and spreadability tests, while antibacterial activity was assessed using the disc diffusion method. Data were analyzed with Shapiro–Wilk, Levene’s, One-Way ANOVA, and LSD Post Hoc tests. Results and Discussion: All formulations met physical quality standards. Antibacterial testing showed inhibition zones of 7.57 mm (moderate) for 15%, 10.67 mm (strong) for 25%, and 13.47 mm (strong) for 35%, with higher concentrations producing greater inhibition. Positive control exhibited a 37.60 mm (very strong) inhibition zone, while the negative control showed no activity. Implications: Red betel leaf extract demonstrates potential as a natural antibacterial ingredient in acne treatment formulations. The 35% concentration was optimal but still less effective than clindamycin. Future research should focus on optimizing formulation stability, enhancing sensory appeal, and exploring synergistic combinations to improve efficacy.